Pengembangan Dan Validasi Metode Analisis Ranitidin Hidroklorida Tablet Dengan Metode Absorbansi Dan Luas Daerah Di Bawah Kurva Secara Spektrofotometri Ultraviolet - Boy Chandra; Harrizul Rivai; Marianis Marianis (Jurnal Farmasi Higea, 2016)
Development and validation of methods of analysis of ranitidine hydrochloride tablets have been done by absorbance method and the method of the area under the curve by ultraviolet spectrophotometry. This study use the principle of calculation of absorbance and the area under the curve obtained from the measurement of the analyte solution by using UV-Vis spectrophotometer and distilled water as the selected solvent. Linearity ranitidine hydrochloride obtained in the concentration range of 6 - 14 ppm with correlation coefficient value by absorbance and the area under curve method respectively 0.99943 and 0.99947. Results of the study showed that the samples of generic ranitidine hydrochloride tablets obtained by absorbance method and the area under curve method was 99.57 ± 0.001 % and 103.30 ± 0.001 %. The average percent recovery obtained by the absorbance and the area under curve method was 98.31 % and 95.39 %. While the research results for the samples of Gasela tablets obtained by the absorbance and the area under curve method was 96.98 ± 0.002 % and 104.33 ± 0.009 %. The average percent recovery obtained by the absorbance method and the area under each curve was 98.89 % and 94.78 %.